Ta có : 6n-44 chia hết cho n-4
=> 6n-24-20 chia hết cho n-4
=> 6(n-4)-20 chia hết cho n-4
=> 20 chia hết cho n-4
=> n-4 thuộc Ư(20)={-20;-10;-5;-4;-2;-1;1;2;4;5;10;20}
=> n thuộc {-16;6;-1;0;2;3;5;6;8;9;24}
Vậy _____
Học tốt!
Ta có : 6n - 44 = 6n - 4 - 40
=> 6n - 4 - 40 chia hết cho n - 4
Mà 6n - 4 chia hết cho n - 4
=> -40 chia hết cho n -4
=> n-4 thuộc Ư(-40)
Mà Ư(-40) = ( -40; -20; -10, -5; -4; -2; -1; 1; 2; 4; 5; 10; 20; 40 )
=> n - 4 thuộc ( -40; -20; -10, -5; -4; -2; -1; 1; 2; 4; 5; 10; 20; 40 )
=> n thuộc ( -36; -26; -6; -1; 0; 3; 5; 6; 8; 9; 14; 24; 44 )